Metode ABA (Applied Behaviour Analysis) : Kemampuan Bersosialisasi terhadap Kemampuan Interaksi Sosial Anak Autis - Hardiani, Ratna Sari; Rahmawati, Sisiliana (Jurusan Keperawatan FIKES UNSOED, 2012)
Autism is a complex development disorder attributed with communication, social interaction, and imagination activity. Disturbance of social interaction on autism could affect learning and behaviour aspects. The study aimed to analyze the influence of applied behaviour analysis method: social ability on autism children's social interaction ability. The study used pre experimental design with one group pretest posttest without control group design. The sample was 15 children, with using total sampling. Data was analyzed with Wilcoxon Match Pair Test. The result showed majority autism children (66,7%) had a less ability of social interaction before intervention (pre test), and majority autism children (53,3%) had enough ability of social interaction after intervention (post test). Data analyzed showed that P value was 0,008 (0,008 pÃ¢â€°Â¤0,05). It can be concluded that there is an influence of applied behaviour analysis method: social ability on autism children's social interaction ability, it is suggested for the family with an autism child to give applied behaviour analysis method: social ability to exercise the autism children's social interaction ability.Ã‚Â